BUKU KIA DAN PEMANFAATAN UNTUK PENINGKATAN KESEHATAN IBU DAN ANAK - Lia Kurniasari (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2017)
MCH Book is one tool that can be used to detect early existence of health problem or health problem in mother and child. The uniform use of MCH Books in Indonesia began in 2006 and is constantly updated up to now. Target Book of KIA is mother and child, starting from pregnant mother until 5-year-old child. KIA books become very concise tools to be learned by every family. The KIA book is a combination of Mother and Child health cards, starting from KMS of pregnant mother, KMS toddler, Family Planning Card, Child Development Card, etc. The KIA book is also used as a tool for effective counseling and communication to the community, and easy to use. The use of MCH books continues to work well throughout the archipelago for the realization of improving the health status of the community especially mother and child.